The Scientific Production of Women and their Presence in Management Position in Science and technology careers in the Ecuadorian Higher Education System - Escobar-Jiménez, Christian; Torres Rentería, Sergio; Delgado, Alejandra (Journal of Education Culture and Society, 2024)
Aim. This paper analyzes the scientific production and the management positions in the universities of the Ecuadorian higher education system from a gender parity perspective, considering STEM careers as the central point of the analysis. Three perspectives was consider,: the underrepresentation of women in STEM careers, the underrepresentation of women in scientific production and in classic managerial positions, and the Norwegian paradox of equality. Methods. This article used two databases: the first one was built from Ecuadorian scientific production, within the period 2010-2018, by the indexing platform SCOPUS. The second one, evaluates the presence of women in management positions and was built from the databases that universities and polytechnic schools report to the educational Ecuadorian autority. Theoretical perspectives are discussed to explore the singularities of the Ecuadorian case, through an analytical and quantitative perspective. Results. In the case of Ecuadorian scientific production men showed a greater presence in all fields, except for pedagogy and psychology. This results replicate for the case of higher education management positions (30% women, 60% men, on average). Conclusions. The underrepresentation of women is generally confirmed, both in scientific production measured by publications, as well as in access to management positions, especially in science and technology. Also, in scientific publications, women are more likely to collaborate only with men, precisely because of the structures created around science, which not only have to do with the greater number of men involved, but probably with gender discrimination practices that are not visible in the mechanisms adopted for the analysis.